(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The explanatory dictionary is intended to contain common and frequently used words of the literary language, to analyze and explain their meanings, as well as to show the lexical and semantic norms of the literary language. The explanatory dictionary provides for the systematization information related to cultural and material wealth in a certain order in the content of both widely used and rarely used words. An explanatory is a type of dictionary that systematizes the vocabulary of a particular language and reveals its meanings. In many words, especially in stable phrases, their meanings accumulate information related to culture, worldview, history, and traditional economics of the nation. Such information contained in the word is disclosed in the explanatory note and clarified with illustrative material. Giving an example is one of the requirements for creating an explanatory dictionary because the examples given in the explanatory dictionary are additional illustrative material, which determines the origin of capital words, their stylistic and semantic, grammatical features. The quoted materials in the dictionary entry prove that the word exists or once existed. The entry shows the attitude of scientists-researchers to the quoted material, the language functions of the examples given in explanatory dictionaries. In the explanatory dictionaries of the Kazakh and Turkish languages, we mention the provision of quoted materials. Key words: illustrative material, verbal illustration, an example, an explanatory dictionary.